Analysis of Sharia Financial Literacy, Self-Control, and Deliberative Thinking on the Financial Behavior of MSMEs in Banda Aceh City - Siregar, Muhammad Rendhie; Umuri, Khairil; Najla, Najla; Amri, Khoirul (Jihbiz: Global Journal of Islamic Banking and Finance, 2025)
This study aims to investigate the impact of Islamic financial literacy, self-control, and deliberative thinking on the financial behavior of MSMEs in Banda Aceh City. This study uses quantitative data consisting of primary and secondary data. The sample of this study consisted of 108 respondents, obtained using the Hair formula. Data analysis used the multiple linear regression test method. The results of this study indicate that the variables of Islamic financial literacy, self-control, and deliberative thinking partially influence financial behavior. Then, simultaneously, the variables of Islamic financial literacy, self-control, and deliberative thinking influence financial behavior among MSMEs in Banda Aceh City. Therefore, to improve financial behavior among MSMEs, greater emphasis should be placed on Islamic financial literacy, self-control, and deliberative thinking to help foster more responsible financial behavior.